2011
DOI: 10.1007/s10452-011-9387-3
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of temperature and nutrient loading to growth rate variation of three cyprinid fishes in a lowland river

Abstract: Scales collected during a maximum of seven fish population surveys over a 25-year period (1983-2008) in the River Wensum, a lowland river in Eastern England, enabled temporal analysis of the growth rates of roach Rutilus rutilus, dace Leuciscus leuciscus and chub Leuciscus cephalus. Across the study period, all species showed temporal variability in their growth patterns. Roach showed a significant temporal decrease in their growth, where rates recorded in surveys in 2005 and 2008 were significantly slower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 45 publications
3
54
2
Order By: Relevance
“…This finding differs from previous studies which have reported a positive trend between WWTW effluent concentration and the size of resident fish (Pottinger et al 2013;Tetreault et al 2012) but is consistent with the results of a study in which the growth of sticklebacks downstream of a WWTW was improved following remediation of the effluent (Pottinger et al 2011). WWTW effluent contains nutrients likely to improve productivity of the downstream aquatic ecosystem and WWTW effluent discharges also tend to raise the water temperature in receiving waters (Brooks et al 2006;Gücker et al 2006), both of which are factors that have a positive effect on the growth of fish (Beardsley and Britton, 2012;Graham and Harrod 2009). However, WWTW effluent also contains chemicals with the potential to exert a negative effect on the growth of fish via direct effects on physiological or endocrine processes, or because the fish need to divert resources to coping with a toxicological challenge (Forbes and Calow 1998).…”
Section: Effluent-related Variation In Fish Size Is Eliminated By Trasupporting
confidence: 76%
“…This finding differs from previous studies which have reported a positive trend between WWTW effluent concentration and the size of resident fish (Pottinger et al 2013;Tetreault et al 2012) but is consistent with the results of a study in which the growth of sticklebacks downstream of a WWTW was improved following remediation of the effluent (Pottinger et al 2011). WWTW effluent contains nutrients likely to improve productivity of the downstream aquatic ecosystem and WWTW effluent discharges also tend to raise the water temperature in receiving waters (Brooks et al 2006;Gücker et al 2006), both of which are factors that have a positive effect on the growth of fish (Beardsley and Britton, 2012;Graham and Harrod 2009). However, WWTW effluent also contains chemicals with the potential to exert a negative effect on the growth of fish via direct effects on physiological or endocrine processes, or because the fish need to divert resources to coping with a toxicological challenge (Forbes and Calow 1998).…”
Section: Effluent-related Variation In Fish Size Is Eliminated By Trasupporting
confidence: 76%
“…Scales were measured for scale radius, distance to last annulus and distance between annulus 1 and 2, with these converted to length at the last annulus and length increment between age 1 and 2 years old by back-calculation (Dahl Lea method; Francis, 1990). Length at the last annulus enabled growth rates over the life time of the fish to be assessed, whilst the increment between age 1 and 2 years enabled assessment of juvenile growth rates (Beardsley and Britton, 2012). Differences in the lengths of the fish sampled by angling and electric fishing were tested using a generalised linear model (GLM), as these data were not normally distributed, with the significance of differences assessed by linearly independent pairwise comparisons with Bonferroni adjustment for multiple comparisons.…”
mentioning
confidence: 99%
“…Firstly, analyses determined the mean standardized growth residuals for each reach according to lengths at the last annulus and length increment between age 1 and 2 years (Beardsley and Britton, 2012). Only one growth metric value per fish was used in each test to avoid pseudo-replication (Beardsley and Britton, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations